2021
DOI: 10.1002/qre.3049
|View full text |Cite
|
Sign up to set email alerts
|

On the location‐based memory type control charts under modified successive sampling scheme

Abstract: The magnificent seven statistical process control (SPC) tools are commonly used to monitor the variation in the process. Control charts are the most efficient and real‐time monitoring tool from the SPC toolkit. A control chart visually differentiates the effect of special or inherent cause variations and indicates the process as out‐of‐control when such a special cause exists. For single occasion problems, simple random sampling (SRS) is used as a sampling design. When the quality of a product is assessed at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This sampling procedure will be carried out until desired sample size is achieved. Patterson [36], Rao and Graham [37], Choudhary et al [38], Yaqub et al [32], Abbas et al [33] and Hyder et al [34] described some modifications of successive sampling.…”
Section: Modified Successive Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…This sampling procedure will be carried out until desired sample size is achieved. Patterson [36], Rao and Graham [37], Choudhary et al [38], Yaqub et al [32], Abbas et al [33] and Hyder et al [34] described some modifications of successive sampling.…”
Section: Modified Successive Samplingmentioning
confidence: 99%
“…The modified form of the successive sampling scheme is more effective than other existing sampling techniques and is specially designed to monitor process parameters (location or dispersion). For the real-time surveillance of the location parameter, memory-type control charts based on MSS were designed by Hyder et al [34].…”
Section: Introductionmentioning
confidence: 99%
“…Riaz et al [31] showed that the linear profile monitoring methods under the MSS scheme outperformed the SRS schemes linear profile monitoring methods. Recently, Hyder et al [17] introduced new moving average control charts based on the MSS scheme for monitoring the processs dispersion parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the generally weighted moving average (GWMA) and its extension as a double GWMA chart based on exceedance statistics are proposed by Chakraborty et al 17 and Masoumi Karakani et al 18 Researchers highly prefer CUSUM charts as they contain information about historical observations like EWMA charts. 19 Generally, CUSUM charts outperform Shewhart charts in detecting small shifts; see Hyder et al 20 On the other hand, the in-control (IC) robustness of parametric CUSUM charts is insufficient. 21 Therefore, there have been many studies related to univariate nonparametric CUSUM charts.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers highly prefer CUSUM charts as they contain information about historical observations like EWMA charts 19 . Generally, CUSUM charts outperform Shewhart charts in detecting small shifts; see Hyder et al 20 . On the other hand, the in‐control (IC) robustness of parametric CUSUM charts is insufficient 21 .…”
Section: Introductionmentioning
confidence: 99%